2010
DOI: 10.1074/jbc.m109.058347
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus Skip Modulates Wnt/β-Catenin Signaling and Functions in Neural Crest Induction

Abstract: The ␤-catenin-lymphoid enhancer factor (LEF) protein complex is the key mediator of canonical Wnt signaling and initiates target gene transcription upon ligand stimulation. In addition to ␤-catenin and LEF themselves, many other proteins have been identified as necessary cofactors. Here we report that the evolutionally conserved splicing factor and transcriptional co-regulator, SKIP/SNW/NcoA62, forms a ternary complex with LEF1 and HDAC1 and mediates the repression of target genes. Lossof-function studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Luciferase reporter assay Luciferase reporter assays were carried out in 96-well plates, with triplicates as described previously (Wang et al, 2010a). DNA per well was: PAK1, 50 ng; Rac1 and its mutants, 50 ng; cyclin D1-luciferase reporter construct, 50 ng.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase reporter assay Luciferase reporter assays were carried out in 96-well plates, with triplicates as described previously (Wang et al, 2010a). DNA per well was: PAK1, 50 ng; Rac1 and its mutants, 50 ng; cyclin D1-luciferase reporter construct, 50 ng.…”
Section: Methodsmentioning
confidence: 99%
“…Protein stability assay, co-immunoprecipitation assay and western blot Protein stability assay, western blot and co-immunoprecipitation experiments were performed as described previously (Wang et al, 2010a). To detect the interaction between endogenous PAK1 and b-catenin, SW480 cells were lysed with RIPA buffer (50 mM Tris-HCl pH 7.4, 150 mM NaCl, 1% NP40, 0.25% sodium deoxycholate, 0.1% sodium dodecyl sulfate, 1 mM dithiothreitol, supplemented with protease inhibitor cocktail, 2 mM Na 3 VO 4 and 25 mM NaF) and lysates were immunoprecipitated with anti-PAK1 antibody.…”
Section: Methodsmentioning
confidence: 99%
“…For X. laevis tmem198, the primers were 5Ј-TGAACAGTTTTATCACCCGCC-3Ј and 5Ј-TATTATGACA TCAGTATGAGAGAA-3Ј. Other primers were used as previously described (51).…”
Section: Methodsmentioning
confidence: 99%
“…The MO sequences of Xenopus laevis tmem198 (NM_001094258) were as follows: MO-1, CGGTGGGACAACAGAC GATAGATCA; MO-2, GAATCTGGTGTTAAGTAAGCATGTC. Wholemount in situ hybridization and LacZ staining were performed as described previously (51). RNA probes were hybridized at 60°C, and BM purple substrate (Roche) was applied for the chromogenic reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Co-injection of Xkctd15 did not reduce the frequency or completeness of Wnt8-induced axis duplications (data not shown). A recent study showed that an activator of Wnt signaling, Skip (1-341), was inefficient in inducing axis duplications (Wang et al, 2010), suggesting that certain modulators of Wnt signaling are inefficient in early frog embryos. In zebrafish, cells responsive to b-catenin can be monitored in the transgenic TOP-dGFP reporter line (Dorsky et al, 2002).…”
Section: Kctd15 Function Is Conserved and Inhibits Nc Induction In Exmentioning
confidence: 99%